2019
DOI: 10.24926/iip.v10i3.1774
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and Community Pharmacists’ Perceptions of Online Pharmacy Services in Uyo Metropolis, Nigeria

Abstract: Background: Online pharmacies benefit consumer healthcare experience through affording convenience, efficiency, greater confidentiality, and improved access to medicines. There are several online pharmacies in Nigeria, however, studies about their use as well as consumer and pharmacists’ perceptions of the service are lacking. Objective: This study aimed to evaluate community pharmacists’ and consumer perceptions of online pharmacy services (OPS) in Uyo metropolis, Nigeria. Method: This was a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Research shows that prior experience of purchasing goods online ( Fittler et al, 2018 ; Ndem et al, 2019 ); online shopping experience ( Hu et al, 2021 ); comfort with the network transaction environment ( Hu et al, 2021 ); greater health literacy, that is ability to find, understand, and use information needed to purchase from online pharmacies ( Sabbir et al, 2021 ); lower electronic health literacy ( Ivanitskaya et al, 2010 ); awareness of online pharmacy website technology ( Alsadoun et al, 2023 ); and consumers’ expertise regarding online pharmacies ( Wiedmann et al, 2010 ) were positively associated with purchase intentions. Personal experience also influenced OTC medication purchase behavior ( Anis and Tan, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that prior experience of purchasing goods online ( Fittler et al, 2018 ; Ndem et al, 2019 ); online shopping experience ( Hu et al, 2021 ); comfort with the network transaction environment ( Hu et al, 2021 ); greater health literacy, that is ability to find, understand, and use information needed to purchase from online pharmacies ( Sabbir et al, 2021 ); lower electronic health literacy ( Ivanitskaya et al, 2010 ); awareness of online pharmacy website technology ( Alsadoun et al, 2023 ); and consumers’ expertise regarding online pharmacies ( Wiedmann et al, 2010 ) were positively associated with purchase intentions. Personal experience also influenced OTC medication purchase behavior ( Anis and Tan, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fittler et al (2018);Ndem et al (2019) Personal experience Anis and Tan,(2023) Comfort with the network transaction environmentHu et al (2021) Years of experience with online shoppingHu et al (2021) Greater health literacy (ability to find, understand, and use information needed to purchase from online pharmacies) Sabbir et al(2021) Lower electronic health literacyIvanitskaya et al (2010) Awareness of online pharmacy website technology Alsadoun et al(2023) Consumer is an enthusiastic expert about online pharmacies Wiedmann et al(2010) Health insuranceNo healthcare coverage Cicero and Ellis, (2012) Have higher health care expenditures Brown and Li, (2014) More likely to be privately insured Brown and Li, (2014) Medicaid insurance coverage Brown and Li, (2014) Health insurance coverage Desai et al (2015) Privacy Anonymity Cicero and Ellis, (2012) More privacy Alwhaibi et al (2021); Almomani et al (2023) Do not want to discuss with doctor Koenraadt and van de Ven, (2018) Product Product quality Holiday-Goodman et al (2007); Van Buskirk et al (2016) Product varieties Alwhaibi et al (2021); Almohammed et al (2023) Note: Italicized text indicates reported findings that are negatively related to purchase intention and behavior.…”
mentioning
confidence: 99%
“…This could show that such online pharmacies are illegal (30). Illegal pharmacies can pose direct and indirect risks to patients and shoppers (10). It shows inconsistency in the use and compliance with international standards and rules in online pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…Online pharmacies refer to online service providers and retailers of medicines, goods, and health-related services. These services offer considerable benefits including convenience and efficiency, competitive price, accessibility, privacy, and door-to-door delivery without geographical restrictions unlike traditional pharmacies (10). Local pharmacy websites are becoming more and more prevalently known as an online "healthcare center", where patients can submit electronic prescriptions, order prescribed and over-the-counter medications, consult pharmacists about a chronic disease, get a prescription for a minor illness, and download the software.…”
mentioning
confidence: 99%